A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Madurai, India - Kiruthiga, Mahendran; Sivaruban, T.; Jeyapriya, Velmurugan; Barathy, S.; Isack, Rajasekaran (Zootaxa, 2026)
Caenis srinii sp. nov. is described from the Karuppayurani pond in Madurai, Tamil Nadu, South India based on larval, subimaginal, and imaginal stages. Diagnostic characters of the new species include distinctive male genitalia, larval setation patterns, and chorionic egg structures. The total number of Caenis species recorded from India is thus raised to fourteen. The most closely related species to C. srinii sp. nov. is Caenis limai Srinivasan, Sivaruban, Barathy & Isack, 2023, and C. ulmeriana Malzacher, 2015. Detailed comparisons with these two species and an updated key of the genus Caenis of south India are provided herein.